Origin of Fish Biomass in a Diverse Subtropical River: An Allochthonic-Supported Biomass Increase Following Flood Pulses - González-Bergonzoni, Ivan; D’Anatro, Alejandro; Vidal, Nicolás; Stebniki, Samanta; Tesitore, Giancarlo; Silva, Ivana; de Mello, Franco Teixeira (Ecosystems (New York), 2019)
The origin of resources supporting metazoan biomass in rivers has long been a subject of debate. The river wave concept (RWC) postulates that the energetic basis of food webs varies along its spatial–temporal location with respect to flow pulses. According to the RWC, river flow determines carbon assimilation in food webs, but this may also depend on river geomorphology. However, studies testing this theory are scarce, particularly those from large subtropical rivers. To analyse the origin of fish biomass in areas of differing geomorphology, we combined stable isotope analysis with standardised measurements of biomass of a diverse fish assemblage along the lower Uruguay River. Furthermore, using 14 years of monitoring data, we tested for relationships between the biomass of species dominantly fuelled by allochthonic resources and the river flow. Fish biomass was dominantly allochthonous-derived along most of the studied sites. At all trophic levels, autochthonous-derived fish biomass was the highest in an upstream anabranch functional process zone (FPZ) (fuelling 54% of the total biomass), while allochthonous-derived biomass prevailed downstream, in the widest sections of an unconstrained lowland FPZ (fuelling 64–72% of the total biomass). Moreover, the dominant species that derived most of its biomass from allochthonous resources (Prochilodus lineatus) increased its biomass following flood pulses. This study supports the RWC statements that, at a spatial scale, local river geomorphology affects fuelling sources for food webs (probably by determining contrasting resource availability scenarios) and, at a temporal scale, increases in the allochthonous fraction of biomass are driven by flood pulses.